DEFINITION OF TECHNIQUES FOR EMOTIONAL STATE ASSESSMENT - Kurbanov, Abdurahmon (Science technology&Digital finance, 2023)
This article aims to provide algorithmic insights into the evaluation of human emotions, highlighting the progress that has been made and the challenges that still exist. By utilizing machine learning algorithms and sentiment analysis, researchers have been able to uncover valuable information about the emotions that robots can express and how they impact consumers. This cross-disciplinary study paves the way for next-level social, design, and creative experiences in artificial intelligence research, particularly in the realms of consumer service and experience contexts.